PERENCANAAN STRATEGIK SISTEM INFORMASI DAN TEKNOLOGI INFORMASI PERGURUAN TINGGI STUDI KASUS: UNIVERSITAS INDRAPRASTA PGRI - Abdul Mufti (LPPM, 2011)
Information is a strategic commodity nowaday. The strategy must be applied in the private or public education by increasing more in local content and bargaining power to the society. University of Indraprasta PGRI where the author conducted a research is a big enough university in providing the educational services. The method used in this research is naturalistic or in qualitative, the author as the key instrument examines the natural object, the technique used for the data collecting is inductive.The results of this research is a formula of strategic planning of information system (IS) and information technology (IT) that is integrated to make it easier for the management to manage the resources to produce the acquired information, more accurate and can be used for all sides. So that, the system can be proposed, implemented and used by University of Indraprasta PGRI. Keywords: Planning, Strategy, Information System, Information Technology, University of Indraprasta PGRI.